2019
DOI: 10.1039/c8pp00403j
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation induced emission of diketopyrrolopyrrole (DPP) derivatives for highly fluorescent red films

Abstract: Triphenylamine moieties substituted diketopyrrolopyrrole derivatives showed highly emissive characteristics in solid film state by aggregation induced emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Methoxy substituted TPA molecule exhibited highest fluorescence quantum in thin film, followed by the phenyl and then naked substituents. [162] This work clearly demonstrated the AIE behaviour for such kind of materials. Afterwards, a series of analogous materials based on TPA and DPPh units with diverse side groups on TPA or DPPh were developed.…”
Section: Luminescent Materialssupporting
confidence: 56%
“…Methoxy substituted TPA molecule exhibited highest fluorescence quantum in thin film, followed by the phenyl and then naked substituents. [162] This work clearly demonstrated the AIE behaviour for such kind of materials. Afterwards, a series of analogous materials based on TPA and DPPh units with diverse side groups on TPA or DPPh were developed.…”
Section: Luminescent Materialssupporting
confidence: 56%
“…Here, we employed η QY of 31% which is the same as of the experimentally measured value. 47 The analytical model calculates the η opt values based on the emissions from all edges of the LSC device as illustrated in configuration C (Supporting information, Figure S1). The results suggest that η opt declines with the increasing length of LSC under different light conditions (Figure 5A).…”
Section: Measurementsmentioning
confidence: 99%
“…4-yl)amino)benzldehyde (TPE-TPA-CHO), and compounds 1-7 were prepared efficiently according to the literatures. [45][46][47] 4-(Diphenylamino)phenylboronic (TPA-BO) acid was obtained from TCI, Japan, and was used without further purification. The rest of the chemicals were acquired from local suppliers and utilized as received.…”
Section: Introductionmentioning
confidence: 99%
“…DPPs are gaining a prominent position among organic dyes for optics and electronics thanks to their simple synthesis, intense color, high photostability, and good charge transport properties. 6,7 Several studies have been reported on the control of the DPP aggregation varying the conjugation of the core or the N-substitution, [8][9][10][11] while less explored is the impact on the DPP self-assembly given by the presence of terminal non-conjugated exible chains. 12,13 In our previous works we observed that varying the length of terminal aliphatic side chains (C 8 vs. C 16 ) in a donor-acceptor-donor (DAD) triazole-thiophene-DDP derivative, it was possible to induce the formation of H-or J-aggregates in thin lms and organic nanoparticles (ONPs).…”
mentioning
confidence: 99%